TINGKAT KEBISINGAN DAN TAJAM DENGAR PETUGAS GROUND HANDLING DI BANDARA NGURAH RAI BALI - Putra Yadnya, I W; Adi Putra, N; Redi Aryanta, I W (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2, 2012)
Ngurah Rai Airport is an International Airport in Bali, this will increase the air traffic frequency and increase the number of aircraft types. This condition increases the noise risk factor which contributes to probable cause of health problem for airport workers. The objective of this study is to analyze the noise effect against hearing acurity of the ground handling staff in Ngurah Rai Airport.This cross sectional study design with 44 number of sample. The sample was taking by proportional random sampling method.The study results showed that noise level in the Administration Division was between 49.6 – 52 dBA. However, in the Technical Division at 08.00 – 16.00 was averagely between 88,3 – 90.9 dBA, at 16.00 – 24.00 was between 89.3 – 93.5 dBA and at 24.00 – 08.00 was between 69.9 – 73.2 dBA. Hearing acurity of ground handling staff in the administration division was 1 personnel (16.7 %) experienced hearing acurity depreciation. However, in the technical division, 23 personnel (60.5%) experienced hearing acurity depreciation. The staff with ? 20 years working period numbering 6 personnel (37,5%) experienced hearing acurity depreciation and staff with > 20 years working period numbering 17 personnel (77.3%) experienced hearing acurity depreciation. On the other hand, personnel that always wear hearing protective equipment numbering 7 personnel (33.3%) experienced hearing acurity depreciation and personnel who where not wear hearing protective equipment numbering 16 personnel (94.1%) experienced hearing acurity depreciation.The study concluded that noise level in the administration division was under threshold limit value, in technical division between 08.00 – 16.00 and 16.00 – 24.00 was upper threshold limit value but between 24.00 – 08.00 was under threshold limit value. There was a different hearing acurity between administration division staff and the technical division staff. The study also enlighten there was association between working period and wearing personal protective hearing.
Keywords: noise level, hearing acurity, ground handling staff